Stomatal Development and Conductance of a Tropical Forage Legume Are Regulated by Elevated [CO2] Under Moderate Warming - Habermann, Eduardo; Dias de Oliveira, Eduardo A.; Contin, Daniele Ribeiro; San Martin, Juca A. B.; Curtarelli, Lucas; Gonzalez-Meler, Miquel A.; Martinez, Carlos Alberto (Frontiers in Plant Science, 2019)
The opening and closing of stomata are controlled by the integration of environmental and endogenous signals. Here, we show the effects of combining elevated atmospheric carbon dioxide concentration (eCO2) (600 µmol mol-1) and warming (+2 C) on stomatal properties and their consequence to plant function in a Stylosanthes capitata Vogel (C3) tropical pasture. The eCO2 treatment alone reduced stomatal density, stomatal index, and stomatal conductance (gs), resulting in reduced transpiration, increased leaf temperature, and leading to maintenance of soil moisture during the growing season. Increased CO2 concentration inside leaves stimulated photosynthesis, starch content levels, water use efficiency, and PSII photochemistry. Under warming, plants developed leaves with smaller stomata on both leaf surfaces; however, we did not see effects of warming on stomatal conductance, transpiration, or leaf water status. Warming alone enhanced PSII photochemistry and photosynthesis, and likely starch exports from chloroplasts. Under the combination of warming and eCO2, leaf temperature was higher than that of leaves from the warming or eCO2 treatments. Thus, warming counterbalanced the effects of CO2 on transpiration and soil water content but not on stomatal functioning, which was independent of temperature treatment. Under warming, and in combination with eCO2, leaves also produced more carotenoids and a more efficient heat and fluorescence dissipation. Our combined results suggest that control on stomatal opening under eCO2 was not changed by a warmer environment; however, their combination significantly improved whole-plant functioning.